Strategies for Effective Application Deployment and Scaling in Multi-Cloud Environments - Venkat Marella, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In order to expedite the process and produce high-calibre software at lightning speed, this study explores a DevOps-driven solution created especially for cloud application deployment. A well-chosen stack of technologies forms the foundation of our approach. The powerful version control system Git guarantees smooth code management and teamwork, allowing developers to work simultaneously and easily roll back to earlier iterations. This covers workflow orchestration strategies, data dissemination strategies, and cloud service selection and combination. Real-world AI applications in various cloud settings are used to develop and evaluate the framework. The suggested solutions' efficacy is assessed using performance indicators including latency, throughput, and cost-efficiency. Businesses may save money and take advantage of the benefits provided by various cloud providers by installing tools, putting procedures in place, and regularly monitoring tools. Additionally, the difficulties in maintaining multi-cloud infrastructure may deter IT operations as multi-cloud adoption becomes more widespread in IT organizations. This article encourages the adaptation of the DevOps paradigm to multi-cloud scenarios by emphasizing how it may simplify and ease application development, delivery, and maintenance. By highlighting how the DevOps methodology may facilitate and streamline application development, delivery, and maintenance, this article promotes its extension to multi-cloud situations. While adopting. By improving team communication and boosting productivity across the software product lifecycle, this strategy enables businesses to automate the delivery of high-quality software capabilities. In order to meet the need for new goods and technology, the study issue illustrates how organizational workloads are shifting towards automation, primarily with relation to cloud-based applications. Ensuring the security of workloads across many cloud platforms is crucial in this trend of multi-cloud deployments so that organizational focus is possible. Disparities in deployment strategies, architecture, tools, and procedures provide difficulties even when security measures may be the same. Cloud Security Posture Management (CPSM) solutions address security visibility, which is made more difficult by the cloud's dynamic nature. As an organization's cloud footprint grows, these solutions are essential for supplying visibility. This thorough examination explores the intricacies of multi-cloud deployments in DevOps, offering insights into the difficulties and tactics used to deal with this environment.
Keywords: Cloud Security Posture Management (CPSM); Organizations’; Cost-Efficiency; DevOps; AI Applications; Multi-Cloud Adoption; DevOps-Driven; Cloud Deployments; IT Operations; Team Communication; Software Capabilities.